DESIGN AND IMPLEMENTATION OF AN 11-ELEMENT YAGI ANTENNA AS AN INTERNET SIGNAL BOOSTER IN MENYABO VILLAGE - Setiawan, Geri; Kusumawardhani, Eka; Suryadi, Dedy (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2025)
The Yagi antenna is a type of directional antenna designed to enhance signal reception and transmission in a specific direction. In this study, the MMANA-GAL software was utilized to design and simulate the antenna with a high level of accuracy. The aim of this research is to design and implement an 11-element Yagi antenna capable of capturing signals from a Base Transceiver Station (BTS) to improve weak signal quality in Menyabo Village. Antenna testing was conducted using the MMANA-GAL application for simulation, along with SpeedTest and GNetTrack (GNet-WiFi) applications for measuring signal performance. Based on the results of the design, simulation, and testing phases, it can be concluded that the designed antenna meets the desired specifications. Simulation results indicate that the 11-element Yagi antenna has an impedance of 50 Ohms, a VSWR value of 1:1.00, and a gain of 12.8 dBi. Field testing results demonstrated improved signal performance. Prior to connecting the antenna, SpeedTest results showed a ping of 61 ms, download speed of 0.40 Mbps, and upload speed of 1.70 Mbps. After connecting the antenna at a height of 10 meters, the values improved to a ping of 39 ms, download speed of 1.06 Mbps, and upload speed of 1.46 Mbps. At 12 meters, the results further improved to a ping of 38 ms, download speed of 2.67 Mbps, and upload speed of 1.58 Mbps. Regarding RSSI measurements, before connection, the signal strength was -77 dBm. After connecting the antenna, the RSSI improved to -51 dBm at 10 meters and -41 dBm at 12 meters. Based on these findings, it can be concluded that the designed 11-element Yagi antenna successfully enhances signal quality and meets the targeted specifications.